Variation in energy density of Loricariichthys platymetopon (Siluriformes: Loricariidae) in the upper Paraná River basin - Garcia,Daniela Aparecida (2010)
The present study described the variations in energy density from skeletal muscles of Loricariichthys platymetopon in relation to body size, sex, gonadal development stages, sampling site and habitat type (lotic, semi-lotic and lotic). Samplings were performed between June 2002 and August 2006 in points located in the upper Paraná River floodplain, Rosana Reservoir and Diamante Stream. The energy density from each muscle sample of 212 specimens was determined using an adiabatic calorimeter. The correlations between the variables 'muscle energy density' and 'specimen standard length' were not significant. Only in the Rosana Reservoir there was a significant difference in energetic means between 'sex'. Otherwise, due to the gonadal development stage, a significant difference between energetic means was recorded only for males from the upper Paraná River floodplain and for both sexes in Rosana Reservoir. The density of muscle energy ranged from 4,170 to 5,540 cal/g DW (dry weight), with the means (± standard deviation) of 5,140± 0.06 cal/g DW in the Reservoir, 4,950±0.25 cal/g DW in the stream and 4,920 ±0.18 cal/g DW in the floodplain. Furthermore, we also detected a significant difference between the energy means from the different sampled sites, but the same was not registered among the analyzed habitats. In conclusion, the variation in muscle energy density from L. platymetopon may occur. The occurrence of variation between the sexes depends on the site, and the density variation among the stages depends on both the site and 'sex'. In summary, the spatial variation in muscle energy density from this species strengthens the idea that this factor is not a constant parameter, so it should not be applied in bioenergetics modeling and in the quantification of energetic balance as an unique value.